2020
DOI: 10.1002/ehf2.13096
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the H2FPEF score in patients undergoing transcatheter aortic valve implantation

Abstract: Aims The aim of this study was to assess the prognostic value of the H2FPEF score in patients undergoing transcatheter aortic valve implantation (TAVI) for severe aortic stenosis (AS) and preserved left ventricular ejection fraction (EF). Methods and results In this multicentre study, a total of 832 patients from two German high‐volume centres, who received TAVI for severe AS and preserved EF (≥50%), were identified for calculation of the H2FPEF score. Patients were dichotomized according to low (0–5 points; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
1
16
3
Order By: Relevance
“…It proved its value as an independent predictor of adverse outcomes [18]. Contrary to our results regarding the HFA-PEFF score, a higher H2PEF score acted as an independent predictor of adverse cardiovascular and heart failure outcomes among patients with preserved EF undergoing TAVI [19].…”
Section: Discussioncontrasting
confidence: 96%
“…It proved its value as an independent predictor of adverse outcomes [18]. Contrary to our results regarding the HFA-PEFF score, a higher H2PEF score acted as an independent predictor of adverse cardiovascular and heart failure outcomes among patients with preserved EF undergoing TAVI [19].…”
Section: Discussioncontrasting
confidence: 96%
“…This was also observed in the study using the H 2 FPEF score in TAVI patients. 23 It should be noted that the HFA-PEFF score in our study was presumably still influenced by the haemodynamic effects caused by long-standing AS. Based on our study design, caution should thus be exercised when making a definitive diagnosis of HFpEF in our patient cohort despite the fact that the patient characteristics are highly indicative of HFpEF.…”
Section: Discussionmentioning
confidence: 54%
“…A recent study found that the H 2 FPEF score, another score that has been developed to facilitate the diagnosis of HFpEF, was an independent predictor of all-cause mortality and a composite of cardiovascular mortality or heart failure rehospitalization in patients with preserved ejection fraction undergoing TAVI. 23 The H 2 FPEF score is based on evaluation of clinical and echocardiographic characteristics, whereas the HFA-PEFF score includes echocardiographic morphological and functional parameters and a biomarker. 12,24 In contrast to the aforementioned study, the parameters for the calculation of the HFA-PEFF score in our analysis were obtained after TAVI, that is, after the correction of AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Regarding the H2FPEF score, research attention has shifted from diagnostic markers for HFpEF to prognostic markers in a broad spectrum of heart diseases. [16][17][18] In addition, the Atherosclerosis Risk in Communities (ARIC) study used the H2FPEF score with community participants with no other common cardiopulmonary causes of dyspnea and found increase in the incidence of HF hospitalization or deaths with increasing L ower extremity artery disease (LEAD) is an arterial occlusive disease of the lower limb arteries associated with increased morbidity and mortality. [1][2][3][4][5] Despite advances in revascularization of LEAD, chronic limbthreatening ischemia (CLTI) in end-stage LEAD remains an important medical issue, resulting in limb amputation and extremely high mortality rates.…”
mentioning
confidence: 99%